THE ROLE OF WOMEN IN THE MILITARY MOVEMENT - Khasanova Barno Yusupovna (Galaxy International Interdisciplinary Research Journal, 2022)
One of the founders of Uzbek literature of the 20th century, Hamza Hakimzada Niyazi, in the drama "Poisonous Life, or Victims of Love" says "Violence is prohibited in Sharia", "There is justice in Sharia", "Islam does not die" in the language of Maryam Khan. The creator Maryamkhan fills her works with ideals and contributes to the motivation of women to study and teach.In the prose work "Yangi Saodat", the drama "Creativity of Maysara" and several lyric poems, he shows that the light of the female mind is able to illuminate any darkness.In the view of the ancients, the upbringing of educated women was destined to contribute to the development culture of the entire people of Turkestan.At the same time, such ideas were put forward as to force girls and women to write and read in their native language and increase their literacy.The fact that we remember the works of Sophizoda "Read, mothers", "Uzbek young lady", ladies", "Muslim women" - the proof of our opinion. During the Russian Empire, the Jadids expressed their opinions about women’s education, the age of marriage, and the social role of women in publications in the Turkic language. This later, in the 1920s, prompted Uzbek women activists to develop their reform programs.